2021
DOI: 10.4048/jbc.2021.24.e53
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, Anthropometric Measures, Smoking and Physical Activity Mediate the Causal Pathway From Education to Breast Cancer in Women: A Mendelian Randomization Study

Abstract: Purpose We aimed to investigate whether obtaining a higher level of education was causally associated with lower breast cancer risk and to identify the causal mechanism linking them. Methods The main data analysis used publicly available summary-level data from 2 large genome-wide association study consortia. Mendelian randomization (MR) analysis used 65 genetic variants derived from the Social Science Genetic Association Consortium as instrumental variables for years o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Such a trend has been also reported for the education ( 83 , 84 ). However, a recent study using casual mediation analysis concluded that a low educational level is a causal risk factor in the BC development “as it is associated with poor lipid profile, obesity, smoking, and types of physical activity” ( 85 ). The protective effect of education with respect to BC survival is also questionable, given the discrepancy between studies ( 83 , 84 , 86 ) and a weak effect-size in the meta-analysis ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a trend has been also reported for the education ( 83 , 84 ). However, a recent study using casual mediation analysis concluded that a low educational level is a causal risk factor in the BC development “as it is associated with poor lipid profile, obesity, smoking, and types of physical activity” ( 85 ). The protective effect of education with respect to BC survival is also questionable, given the discrepancy between studies ( 83 , 84 , 86 ) and a weak effect-size in the meta-analysis ( 87 ).…”
Section: Discussionmentioning
confidence: 99%